Studi Kasus: Hubungan Kolaborasi dengan Perilaku Inovatif Guru di Sekolah XYZ - Dianne Finsenda Lika; Floriberta Endar Artika; Tan Triwanti (Magister Teknologi Pendidikan Fakultas Pascasarjana Pendidikan Universitas Pelita Harapan, 2025)
Innovative work behaviour is important for teachers to develop and improve their work effectively. Collaboration is needed to be enhanced so that every teacher can work together to produce quality teaching and learning. The research was an explanatory case studies aims to determine the relationship of collaboration to teacher’s innovative work behaviour at XYZ school. The research was conducted in three days in the 2022/2023 academic year. A closed questionnaire with a four-point Likert scale was given to twenty-two teachers of XYZ school. Pearson’s correlation was used as a validity test Cronbach’s alpha was used as a reliability test and chi square technique was used as a normality test. The data analysis technique used is correlational quantitative data analysis using Spearman’s Correlation (rs). The research results indicate that there is a significant and positive relationship between collaboration and teacher’s innovative work behaviour. In conclusion, collaboration is needed for every teacher to develop their innovative work behaviours.